PERAN DUNIA USAHA DAN DUNIA INDUSTRI TERHADAP ANAK MAGANG JURUSAN TATA BUSANA DALAM MENINGKATKAN KETERAMPILAN MENJAHIT PADA BUSANA WANITA - Mayang Istiqomah (Universitas Muhammadiyah Palembang, 2024)
This research aims to: (1) to know the relationship between the utilization of learning facilities in the business world and the industrial world in the apprenticeship apprentices majoring in fashion, and (2) provide provision to apprentices in the form of increased skills in sewing women's clothing in the form of increased skills in sewing women's clothing. Respondents were industry owners and apprentices. This research method is descriptive qualitative by using data collection techniques, namely interviews, observation, and documentation. The results of this study indicate that the role of the World Business and Industry (DU / DI) is an important role in helping students to develop student skills and gain knowledge at the place of practice and in the industrial world can help provide opportunities for apprentices to learn with adequate facilities apprentices to learn with adequate facilities in the industry with the form of DU / DI relations related to the role of efficient education in supporting the success of the education process in the industry role in supporting the success of the education process at school. The role of DU / DI in the placement of student graduates, by providing information on work needs to SMK through industrial visits, and providing opportunities for students to do prakerin students to do prakerin.Keywords: industry, students, fashion, vocational school